Photoinhibition of Growth in Acanthamoeba castellanii Cultures - Dolphin, Warren D. (1970)
Light from 350 to 680 nm at intensities up to 1.62 × 10(5) ergs per sec per cm(2) slowed exponential growth and lowered the maximum yield in axenic cultures of Acanthamoeba castellanii. Photoinhibition was a linear function of light intensity up to 1.25 × 10(5) ergs per sec per cm(2). At higher intensities, growth was too slow to be measured accurately. A photochemical change occurring in the growth medium on irradiation was a function of light dosage and not intensity per se. Light in dosages which appreciably changed the growth-supporting properties of the medium exceeded the dosages received by exponentially growing cultures during irradiation. Consequently, photoinhibition of growth was attributed to a direct effect of light on the amoebae, not to photodegradation of the medium. The growth-supporting properties of irradiated media could be restored by the addition of yeast extract and Proteose peptone. The reduced growth rate in the light was not due to cyst formation or induction of multinuclearity. Light affected the amoebae either through absorption by intracellular pigment(s) or through binding to the amoebae of a photosensitizing compound in the medium.